A study to ascertain customers' satisfaction on building performance and facilities provided in Polytechnic Kulim - Abdul Wahab, Maszuwita (2005)
Customer satisfaction is very important in every organization's success. This is because customers are the person who judge and evaluate the quality of a business where the customer satisfaction become the mantra for success among all the organizations in today's life. Therefore, customer satisfaction towards building performance will assure an organization to create a high performance building and at the same time understand their customers' requirements and needs. Realizing this, a research had done in Polytechnic Kulim (PKU) where PKU did not know how to measure their customers needs, did not focus on the important customers, did not create good space and environment to the customers etc. To overcome all this problems, the writer constructed a trend of analysis in order to portray the level of satisfaction towards building performance. This is carried out by constructing the questionnaires accordingly in order to achieve the objectives of the study and to analyze the level of satisfaction in order to give an authentic output for this study. In conclusion, the writer has proposed few suggestions for the consideration of PKU in order to be more customer focus that can help the organization to achieve the goals, mission and to be successful in their business.